Natural Resources Management : The Sahelian Operational Review (SOR) - Status Report Two - World Bank (Washington, DC, 2012)
The Sahelian Operational Review (SOR) is a Bank-managed activity, funded by the Government of Norway, that has been in existence since 1990. The objectives of the program were to accelerate the application of operational lessons from natural resources management projects and to seek better information to improve environmental monitoring and reporting systems for such projects in the Sahel.